2009
DOI: 10.1002/malq.200810019
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Elections Broaden Complexity‐Theoretic Resistance to Control

Abstract: Electoral control refers to attempts by an election's organizer ("the chair") to influence the outcome by adding/deleting/partitioning voters or candidates. The groundbreaking work of Bartholdi, Tovey, and Trick [2] on (constructive) control proposes computational complexity as a means of resisting control attempts: Look for election systems where the chair's task in seeking control is itself computationally infeasible.We introduce and study a method of combining two or more candidate-anonymous election scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 48 publications
(152 reference statements)
3
49
0
Order By: Relevance
“…Winners in these three systems are not necessarily unique and these three winner problems ask whether a given candidate is a winner. However, as mentioned earlier, Hemaspaandra, Hemaspaandra, and Rothe [HHR06] have shown that the unique winner problems for Dodgson, Young, and Kemeny elections are Θ p 2 -complete as well. Θ p 2 -completeness suggests that the relevant problem is far from being efficiently solvable, and there are many ways in which completeness for this higher level of the polynomial hierarchy speaks more powerfully than would completeness for its kid brother, NP [HHR97b].…”
Section: Dodgson-winnermentioning
confidence: 82%
See 1 more Smart Citation
“…Winners in these three systems are not necessarily unique and these three winner problems ask whether a given candidate is a winner. However, as mentioned earlier, Hemaspaandra, Hemaspaandra, and Rothe [HHR06] have shown that the unique winner problems for Dodgson, Young, and Kemeny elections are Θ p 2 -complete as well. Θ p 2 -completeness suggests that the relevant problem is far from being efficiently solvable, and there are many ways in which completeness for this higher level of the polynomial hierarchy speaks more powerfully than would completeness for its kid brother, NP [HHR97b].…”
Section: Dodgson-winnermentioning
confidence: 82%
“…In fact, at the time the table's work on control was completed (early 2005), no system was proven to be immune-or-resistant to all twenty types of control (or even to the ten constructive types, or to the ten destructive types). However, recently, work of Hemaspaandra, Hemaspaandra, and Rothe [HHR06] has shown how to "hybridize" collections of elections in a way such that the hybrid election has a polynomial-time winner problem if all its constituent systems have polynomial-time winner problems, yet the hybrid system is resistant to every one of the twenty types of control to which one or more of its constituent systems is resistant. Simply put, the hybridization scheme combines strengths without adding weaknesses.…”
Section: Complexity Of Control: Making Someone Win or Keeping Someonementioning
confidence: 99%
“…Since by Theorem 3.1, Copeland 0.5 provides resistance for all ten basic constructive control types and for CCAC u , and also for the four basic types of destructive voter control, the hybrid (in the sense of [9]) of plurality with Copeland 0.5 is resistant to each basic type of constructive and destructive control and in addition to constructive and destructive AC u control. This result follows via Theorem 3.1 and the results of Hemaspaandra et al [9]. And, unlike the hybrid system constructed by Hemaspaandra et al [9], this hybrid uses only natural systems as its constituents.…”
Section: Overview Of Resultsmentioning
confidence: 97%
“…One key issue here is that there might be attempts to influence the outcome of elections. Settings in which such influence on elections can be implemented include manipulation [3,13], electoral control [2,7,8,9,13], and bribery [6,7]. Although reasonable election systems typically are susceptible to these kinds of influence (for manipulation this is universally true, via the Gibbard-Satterthwaite and Duggan-Schwartz Theorems), computational complexity can be used to provide some protection in each such setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation